2008
DOI: 10.3171/foc/2008/24/2/e15
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of superficial temporal artery–middle cerebral artery bypass for patients with moyamoya disease in the US

Abstract: Object The authors report the long-term results of a series of direct superficial temporal artery–middle cerebral artery (STA–MCA) bypass procedures in patients with moyamoya disease from the western US. Methods All patients with moyamoya disease treated at the University of Washington from 1990 through 2004 (39 patients) were included in this study. Patients underwent pre- and postoperative evaluation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
77
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(82 citation statements)
references
References 24 publications
5
77
0
Order By: Relevance
“…However, because revascularization using the indirect procedure often results in insufficient revascularization in adults, the direct/combined procedure has been increasingly used. 1,2,6,9,14,15,26,39,44 A limitation of this study was its retrospective nature. Because our surgical procedure also includes several steps of the indirect procedure (inverting dura matter, suturing temporalis muscle to the dura, and the placement of the pericranial flap), the result cannot be simply interpreted as a direct comparison between the direct STA-MCA bypass and indirect procedure alone.…”
Section: Discussionmentioning
confidence: 99%
“…However, because revascularization using the indirect procedure often results in insufficient revascularization in adults, the direct/combined procedure has been increasingly used. 1,2,6,9,14,15,26,39,44 A limitation of this study was its retrospective nature. Because our surgical procedure also includes several steps of the indirect procedure (inverting dura matter, suturing temporalis muscle to the dura, and the placement of the pericranial flap), the result cannot be simply interpreted as a direct comparison between the direct STA-MCA bypass and indirect procedure alone.…”
Section: Discussionmentioning
confidence: 99%
“…Many series have reported the efficacy of revascularization in this syndrome by using primarily direct superficial temporal artery (STA)-MCA bypass. [82][83][84][85][86][87][88][89] PET studies in Moyamoya disease have demonstrated re- duced CBF and CO 2 response and increased CBV, MTT, and OEF. 90 CBF is significantly lower in patients with Moyamoya disease than in healthy subjects of the same age.…”
Section: Moyamoya Diseasementioning
confidence: 99%
“…1,2 In patients with Moyamoya disease, a progressive narrowing of the supraclinoid internal carotid artery (ICA) and its proximal branches, negative or severely reduced CVR has been used to identify patients who may benefit from surgical revascularization. 3,4 However, the impact of steal phenomenon on normal-appearing brain tissue (ie, in the absence of overt infarction) has not been previously investigated.…”
mentioning
confidence: 99%